PENGEMBANGAN MODUL BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) MELALUI METODE EKSPERIMEN PADA POKOK BAHASAN KOLOID - Rahma Dhani Syah Fitri (Universitas Negeri Medan, 2022)
Abstract: Development of Contextual Teaching and Learning (CTL) Based Modules Through Experimental Methods on Colloidal Subjects. This study aims to (1) determine the level of validation of learning modules on colloidal materials developed based on CTL, (2) determine student responses to CTL-based learning modules through experimental methods on colloidal materials, (3) determine student learning outcomes on CTL-based learning modules. through experimental methods on colloidal materials. This study uses the method (R&D) with the Dick and Carey model at each stage (planning and development, validation, revision (modification), and product testing). The product developed has been validated by 3 expert validators consisting of 2 chemistry lecturers and 1 chemistry teacher. The average result of contextual-based module analysis (CTL) by chemistry lecturers and teachers that has been developed is ± 3.51. This is a very feasible criterion and can be used as teaching material. Based on the assessment of the percentage level of student interest in the module that has been developed, it is 88.67 (very high). Using a CTL-based module on colloidal subjects, student learning outcomes increased to 82.86% with a maximum score of 95 and a minimum of ± 70 and the posttest average of 83 > KKM score of ± 70. Based on hypothesis testing using hypothesis testing, it resulted tcount > ttable that is 11,794 > 1,690.